How responsive are housing markets in the OECD? National level estimates - Cavalleri, Maria Chiara (OECD Economics Department Working Papers, 2019)
The trend rise of house prices in many OECD countries suggests weakness in the adjustment of supply to demand. This paper estimates long-term elasticities of housing supply to prices in OECD countries before exploring their drivers with a focus on policies. It finds a significant association between weaker supply responsiveness and a proxy measure for more restrictive land-use regulation. Besides, tighter rent controls are linked with lower supply elasticities. In turn, weak supply responsiveness implies that house prices rise more following stronger demand. The sensitivity of house prices to household income is also higher in countries that provide larger amounts of tax relief for homeowners